PENERAPAN BALANCED SCORECARD DALAM MENINGKATKAN KINERJA LAZISMU KOTA MALANG - Dian, Adiwibowo; Pradana, Nikko Zein Jaya; Albaasith, Shooma Fikri; Handayati, Puji; Makaryanawati, Makaryanawati (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2025)
This study examines the implementation of the Balanced Scorecard (BSC) in improving the performance of LAZISMU Malang City as a zakat management institution. Using a descriptive qualitative approach, the research analyzes data through four BSC perspectives: financial, customer, internal process, and learning and growth. Results show a decrease in funds in 2023 due to construction allocation, but there was a significant increase in the number of muzakki from 615 (2021) to 793 (2023). Programs were effectively implemented through three main pillars and supported by consistent human resource development. The study concludes that BSC implementation has helped LAZISMU Malang City manage the organization in a more structured and measurable way, reflected in the increasing number of muzakki and program effectiveness.